Triggers For Destination Brand Loyalty Of Millennial Visitors To Natural Tourism Destinations - Heri Setiawan; Rini; Alditia Detmuliati (Jurnal Manajemen, 2024)
This research investigates triggers for destination brand loyalty of millennial visitors to natural tourism destinations. This research focuses on millennial visitors who have come to several natural tourist destinations in Southern Sumatra, with a sample of 110 visitors selected through purposive sampling. The survey output shows that eWoM has no notable effect on the image of a destination brand. However, the quality of the destination brand has a prominent clout on the image of a destination brand. Furthermore, the image of a destination brand significantly affects visitor engagement and loyalty. In addition, visitor engagement has a valuable clout on loyalty. Visitor engagement mediates between the image of a destination brand and a loyalty brand for nature tourism destinations. These findings provide precious insights for marketers of nature tourism destinations, offering alternative strategies to increase and maintain visitor loyalty.